Educational Digital Technologies Development while Covid-19 pandemic - Tatiana M. TATARNIKOVA; Valery M. ABRAMOV; Eugene P. ISTOMIN; Evgeniy A. BAIKOV; Vladimir A. BOLSHAKOV; Ekaterina M. KORINETS; Tatiana V. VEKSHINA; Ernest R. ESTRIN (Communications of International Proceedings, 2020)
In article, we describe the development results of educational digital technologies (EDT) adapted to Covid-19 pandemic conditions. In studies, we used methods of data bases constructing within digital educational platforms, web-technologies and virtual reality tools. While Covid-19 pandemic, we have to work on digital transformation of university education, including creation of new concepts for obtaining and presenting didactical materials. We propose to use digital educational platforms, which integrate heterogeneous hardware and software resources with the use of web-technologies in distributed networks and wide application of cloud services. We propose to use Google Classroom, as essential digital educational platform. Recently, we use remote sensing databases for educational purposes within geo-information management disciplines. We consider the issues of digital content creation within university education, essentially in practical training. We present the enlarged groups of didactical works in this area. For data exchange and preliminary discussion while research, was used platform https://www.researchgate.net/profile/Valery_Abramov2/.
Keywords: Educational Technologies; Digital Transformation; Covid-19 Pandemic; Environmental Economics